2020
DOI: 10.1111/jocd.13840
|View full text |Cite
|
Sign up to set email alerts
|

Fractional CO2 laser therapy for cesarean scar under the guidance of multiple evaluation methods: A retrospective study

Abstract: The cesarean section rate is reported to be 25.3% at a tertiary hospital in Sydney, which increases from 18.7% in 1989-1994 to 30.4% in 2010-2016. 1 Irrespective of the complications, the incision scar of cesarean is the greatest source of annoyance for mothers. Various treatments have been introduced to satisfy the maternal demand for scar therapy, including suture technique, physical therapy, and steroid injection. Of them, laser therapy is promising in the treatment for incision scar. Nowadays, numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…One month after the first and third CO2-AFL treatment, also at 2 and 6 months after the surgery, the Vancouver scar scale (VSS) 19 and the University of North Carolina 4P Scar Scale (UNC4P) 20 of patients were assessed by 2 independent evaluators. The VSS assessed 4 variables: pigmentation, height/thickness, pliability, and vascularity.…”
Section: Methodsmentioning
confidence: 99%
“…One month after the first and third CO2-AFL treatment, also at 2 and 6 months after the surgery, the Vancouver scar scale (VSS) 19 and the University of North Carolina 4P Scar Scale (UNC4P) 20 of patients were assessed by 2 independent evaluators. The VSS assessed 4 variables: pigmentation, height/thickness, pliability, and vascularity.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to appearance, studies of scar healing, such as those using the Vancouver Scar Scale or ultrasound measurement, have demonstrated improvements in the hardness [10,14], thickness [11,16] and flexibility and elasticity [10,14] of scars. In studies of motor function at scar sites [12], studies using the Patient Scar Assessment Questionnaire showed improvements in appearance and scar awareness [10][11][12][13][14][15][16].…”
Section: Preventive Effect Of Pbmt On Scarringmentioning
confidence: 99%
“…Recently, the effectiveness of CO 2 lasers (a fractional CO 2 laser, in particular) for the treatment of epithelial scars from trauma, surgical wounds and acne was reported in clinical studies using biopsy samples [5][6][7][8][9], in studies using a scar scale or a visual analog scale [10][11][12][13][14][15][16] and in basic studies using experimental animals [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%